ANALISIS PENERAPAN PRAKTIK AKUNTANSI MANAJEMEN DALAM MENINGKATKAN EFISIENSI PENGELOLAAN PADA UMKM GARUT - Shofa Nurul Hakim; Mira Amelia; Novie Susanti Suseno (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a vital role in the Indonesian economy, but still face various challenges in financial management. This study aims to analyze the application of management accounting practices in improving management efficiency in MSMEs in Garut Regency. Using a descriptive qualitative research method, the study involved three MSMEs namely Raran Cell, Ladu Bayongbong, and Jajanan Teh Oca as the main informants. Data were collected through interviews and observations with a focus on three aspects: organizing, capital decision-making, and implementation of management accounting practices. The results show that although the three MSMEs still use a simple organizing system, the application of management accounting practices has improved the efficiency of managing their businesses. This research contributes practically to improving efficiency and effectiveness in management accounting practices.